2023
DOI: 10.3390/cancers15174313
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of CDH1, CTNNA1 and CTNND1 Germline Variants in Families with Diffuse and Mixed Gastric Cancer

Joana Guerra,
Carla Pinto,
Pedro Pinto
et al.

Abstract: The most well-characterized hereditary form of gastric cancer is hereditary diffuse gastric cancer (HDGC), an autosomal dominant syndrome characterized by an increased risk of diffuse gastric and lobular breast cancer. HDGC is predominantly caused by germline pathogenic variants in the CDH1 gene, and more rarely in the CTNNA1 gene. Furthermore, the International Gastric Cancer Linkage Consortium (IGCLC) guidelines do not clarify whether or not mixed gastric cancer (with a diffuse component) should be considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Both CDH1 and CTNNA1 are well-established genes associated with HDGC predisposition [ 2 , 35 ], supporting that CTNND1 germline variants could be involved not only in other hereditary syndromes [ 26 30 ] but also in EOGC predisposition. In fact, although CTNND1 was not found altered in a small cohorts of HDGC [ 36 ], a recent study has found up to six variants of unknown significance in CTNND1 in a cohort of 141 GC patients with diffuse and mixed histology [ 37 ]. This finding increases the evidence of the possible involvement of CTNND1 in germline predisposition to EOGC.…”
Section: Discussionmentioning
confidence: 99%
“…Both CDH1 and CTNNA1 are well-established genes associated with HDGC predisposition [ 2 , 35 ], supporting that CTNND1 germline variants could be involved not only in other hereditary syndromes [ 26 30 ] but also in EOGC predisposition. In fact, although CTNND1 was not found altered in a small cohorts of HDGC [ 36 ], a recent study has found up to six variants of unknown significance in CTNND1 in a cohort of 141 GC patients with diffuse and mixed histology [ 37 ]. This finding increases the evidence of the possible involvement of CTNND1 in germline predisposition to EOGC.…”
Section: Discussionmentioning
confidence: 99%